Amalan Pematuhan Prosedur Keselamatan Dan Kesihatan Pekerjaan (KKP) Dalam Kalangan Pekerja Bagi Projek Pembinaan Perumahan Pangsapuri - Abdul Latif, Muhammad Shafiq; Shafii, Haryati; Md Yassin, Azlina; Masram, Haidaliza; Khalid, Zailawati (Research in Management of Technology and Business, 2023)
Apartment housing is among the construction of high-rise buildings that are increasing. However, the construction of high-rise housing has its own risks compared to the risks faced by other constructions. The objective of this study is to identify the practice of compliance with Occupational Safety and Health (OSH) procedures among employees, examine the challenges of complying with OSH procedure compliance practices among employees, and suggest improvements in the management of OSH procedure compliance practices among employees for Apartment housing construction projects. The research method used is the semi-structured interview method. Respondents were selected, namely project managers, safety supervisors, project consultants, and representatives of construction workers in three apartment housing construction projects in Kuala Lumpur. Data were collected through interviews and analyzed using thematic ethnographic methods. The results of the study show that all workers comply with PPE practices well such as the use of PPE followed by the implementation of PPE procedures at the Apartment construction site. As for the challenges, employee management is seen to have problems in applying PPE practices such as a lack of safety supervisors in monitoring workers, and superiors are concerned about the smoothness of the project from a safety aspect. Meanwhile, construction workers have challenges from the aspect of communication and the attitude of different workers at the construction site. As for the recommendations, the   use of drone technology can help supervisors in monitoring labor workers to follow KKP procedures plus the provision of Malay language training for foreign laborers so that they understand the local language and can apply KKP practices better. Keywords: Occupational Safety and Health Procedure Compliance Practices (OSH) for Apartment Housing, Employees